PENERAPAN NSPM BIDANG KESELAMATAN TERHADAP BAHAYA KEBAKARAN DALAM PEMBANGUNAN INFRASTRUKTUR PERUMAHAN DAN PERMUKIMAN - Achmad Hidajat Effendi; Suprapto . (JURNAL STANDARDISASI, 2007)
Basically Ministry of Public Works has issued a number of norms, standard, guidelines and manuals (hereinafter named as NSPM). The questions arises on how far such issued NSPMs particularly related to buildings and housings have fulfilled the need of the users. This is the intention of this research. The methods used comprises survey and interview, gathering field data and proceeded through statistical analysis. The results of research which are focused on SNI 03-1746-2000 concerning means of escape, SNI 03-3989-2000 on sprinkler systems and SNI 03-1745-2000 pertaining standpipe and hose showed a significant data. About 76.5 % of the respondent know these standards, however 42.2 % of the respondent suggested to increase dissemination. 41.9 % of the respondent do not clearly understand the substances. 44.1 % of the respondent suggested to revise the standards, while a more detailed technical guidelines were suggested to be made by 71.4 % of the respondent.